2022
DOI: 10.1021/acssensors.2c00819
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient PTCA/Co3O4/CuO/S2O82– Ternary Electrochemiluminescence System Combined with a Portable Chip for Bioanalysis

Abstract: Herein, we reported an efficient electrochemiluminescence (ECL) biosensor chip for sensitive detection of neuron-specific enolase (NSE). First, 3,4,9,10-perylenetetracarboxylic acid with good luminescence characteristics was used as a luminophore to obtain a stable ECL signal. Subsequently, hollow porous Co3O4/CuO concave polyhedron nanocages (CPNCs) were designed as co-reaction promoters to amplify the luminescence signals for highly sensitive trace detection of NSE. In brief, the rapid cyclic conversion of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Herein, the 5,5-dimethyl-1pyrroline N-oxide (DMPO) free-radical trapping agent was used to analyze the EPR spectrum of the Ag@CuCo 2 O 4 / PTCA-COF/S 2 O 8 2− system. 44,45 As observed in Figure 2D, it was a typical quadruple peak with a peak intensity ratio of 1:2:2:1, which corresponded to the DMPO−OH adducts and confirmed the production of hydroxyl radicals (OH • ). Meanwhile, between the four above-mentioned typical peaks, there were two additional smaller peaks that were indicative of DMPO−SO 4 adducts and showed the existence of SO 4…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…Herein, the 5,5-dimethyl-1pyrroline N-oxide (DMPO) free-radical trapping agent was used to analyze the EPR spectrum of the Ag@CuCo 2 O 4 / PTCA-COF/S 2 O 8 2− system. 44,45 As observed in Figure 2D, it was a typical quadruple peak with a peak intensity ratio of 1:2:2:1, which corresponded to the DMPO−OH adducts and confirmed the production of hydroxyl radicals (OH • ). Meanwhile, between the four above-mentioned typical peaks, there were two additional smaller peaks that were indicative of DMPO−SO 4 adducts and showed the existence of SO 4…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…Furthermore, the ESR spectrum of the Cu 3 (HHTP) 2 /PTCA-COF/S 2 O 8 2– system was tested by using 5,5-dimethyl-1-pyrroline N -oxide (DMPO) as a free radical trapping agent (as shown in Figure C). First, no signals were observed in the Cu 3 (HHTP) 2 and DMPO (curve a) solution whereas a unique hyperfine cleavage of the DMPO-OH adduct (1:2:2:1 quartet pattern) and DMPO-SO 4 adduct appeared in the mixture of K 2 S 2 O 8 and DMPO (curve b), implying the generation of SO 4 ·– (radical ion) and OH (hydroxyl radical). Interestingly, when Cu 3 (HHTP) 2 was added to the S 2 O 8 2– and DMPO solution, the DMPO-SO 4 and DMPO-OH signals were significantly enhanced (curve c), which indicated that Cu 3 (HHTP) 2 could efficiently interact with S 2 O 8 2– as co-reaction accelerators to produce massive amounts of OH and SO 4 ·– . Therefore, we concluded that the enhancement of composite ECL was mainly due to the dual enhancement effect of Cu 3 (HHTP) 2 on the PTCA-COF.…”
Section: Resultsmentioning
confidence: 99%
“…1 NSE is overexpressed in the sera of small cell lung cancer patients (serum concentration >15 ng mL −1 ), 2,3 and is also used for the early diagnosis and prognosis of small cell lung cancer. 4 Many methods have been developed to detect NSE, such as electrochemical sensing, 5 fluorescence immunoassay, 6 photochemistry, 7 resonance light scattering, 8 and electrochemiluminescence. 9 Electrochemiluminescence (ECL) involves photo-excited state energy relaxation and an electrochemical reaction after photon emission during irradiation.…”
Section: Introductionmentioning
confidence: 99%